The Role of Islamic Economics in Indonesia's Growth: Toward Inclusive Development - Misbah, Ibah; Maharajabdinul (Jeksyah: Islamic Economics Journal, 2025)
Islamic economics has emerged as a crucial driver of macroeconomic growth in Indonesia, a country with the world’s largest Muslim population. Over recent years, this sector has demonstrated notable progress, with Islamic banking assets reaching approximately IDR 1,000 trillion in 2024, maintaining a steady annual growth rate of 10-15%. Islamic economics plays a key role in financing small and medium enterprises (SMEs), developing innovative Islamic financial products, and contributing to poverty alleviation efforts. However, challenges persist, including limited public understanding of Islamic financial products, regulatory inconsistencies, and competition with conventional financial institutions. These obstacles hinder the full potential of Islamic economics, but there are significant opportunities, particularly in Islamic investment products and financial technology (fintech), which could serve as catalysts for future growth. Strengthened collaboration between the government, financial institutions, and society is critical to overcoming these challenges and maximizing opportunities for sustainable and inclusive development. This study explores the role, challenges, and prospects of Islamic economics in Indonesia’s macroeconomic growth and provides strategic recommendations to advance the sector towards greater inclusivity and sustainability.